1995
DOI: 10.1007/bf00341207
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal function after low anterior resection of the rectum

Abstract: Impaired neorectal function or sphincter incompetence have been respectively implicated as causative factors of increased frequency of defaecation or incontinence after low anterior resection of the rectum (LARR) for rectal carcinoma, although individual mechanisms of anorectal function have not been fully studied. Functional and laboratory results were evaluated in 19 subjects, who had a LARR for rectal carcinoma before and after the procedure, and were compared to those of normal subjects. LARR worsened anor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 32 publications
2
39
0
4
Order By: Relevance
“…All patients were assessed preoperatively and 6-9 months postoperatively by clinical examination, anorectal manometry, estimation of large-bowel transit, defecography, and ultrasonography of the anorectum according to standard techniques and definitions [14,15]. Their outcome was compared to that of a historical control group of eight female patients, matched for age (71 ± 13 years; range, 51-85 years) and parity, who underwent resection rectopexy through the open approach for overt rectal prolapse (OPEN).…”
Section: Methodsmentioning
confidence: 99%
“…All patients were assessed preoperatively and 6-9 months postoperatively by clinical examination, anorectal manometry, estimation of large-bowel transit, defecography, and ultrasonography of the anorectum according to standard techniques and definitions [14,15]. Their outcome was compared to that of a historical control group of eight female patients, matched for age (71 ± 13 years; range, 51-85 years) and parity, who underwent resection rectopexy through the open approach for overt rectal prolapse (OPEN).…”
Section: Methodsmentioning
confidence: 99%
“…11 However, few studies on the relationship between neorectal evacuation and defecatory function after LAR have been conducted. 12,13 In the present study, scintigraphic assessment of neorectal evacuation was done in patients who underwent LAR with a straight anastomosis. We examined the relationship between neorectal evacuation and clinical defecatory function, clinical factors, and anorectal manovolumetric parameters.…”
mentioning
confidence: 99%
“…The reservoir function of the remaining rectum or the rectal replacement can be quantified with these parameters. A post-operative reduction in these parameters could be measured in patients compared with pre-operatively (5, 25,89,115,123,161), as well as in patients compared with healthy controls (25,39,154,158). Compliance is also influenced by the height of the anastomosis and the length of the rectal stump.…”
Section: Diminished Reservoir Functionmentioning
confidence: 99%
“…Compliance is also influenced by the height of the anastomosis and the length of the rectal stump. Anastomotic leakages (44,115) with consecutive scarring of the wall of the replacement rectum or the remaining rectum and late radiation reactions following adjuvant radio chemotherapy with the formation of a rigid wall in the neorectum naturally also result in reduced compliance, and thus to deterioration in the reservoir function 3.2 Reduction in resting anal pressure (RP) due to stretching trauma Many manometric studies before and after low anterior resection have shown a reduction in resting anal pressure up to one year post-operatively compared with pre-operatively, regardless of whether the reconstruction had been made with a colon pouch or with a straight coloanal or colorectal anastomosis (5, 25,30,37,66,69,72,74,89,158,161). As might be…”
Section: Diminished Reservoir Functionmentioning
confidence: 99%